The Effect of IoT Technology, Real-Time Analytics, and Digital Asset Management on Energy Efficiency and Productivity in Indonesia's Manufacturing Industry - Dwi Setiawan; Budi Sulistiyo Nugroho; Arif Nurrahman; Farid Alfalaki Hamid; Kurniawan Saputra (West Science Social and Humanities Studies, 2024)
This research investigates the impact of IoT (Internet of Things) technology, real-time analytics, and digital asset management on energy efficiency and productivity in the Indonesian manufacturing industry. A quantitative approach, employing structural equation modeling (SEM) with Partial Least Squares (PLS) 3 software, is utilized to analyze survey data collected from manufacturing firms across different sectors and sizes in Indonesia. The results reveal significant positive relationships between digital technologies (IoT, real-time analytics, digital asset management) and energy efficiency/productivity. Specifically, Digital Asset Management, IoT Technology, and Real-Time Analytics are found to have statistically significant effects on enhancing energy efficiency and productivity levels in Indonesian manufacturing operations. These findings underscore the transformative potential of digital technologies in driving operational performance and sustainability in the manufacturing sector. Policymakers, industry stakeholders, and practitioners can leverage these insights to inform strategic decision-making and investments in digital infrastructure, workforce development, and regulatory frameworks to foster innovation and competitiveness in the Indonesian manufacturing landscape.